2011
DOI: 10.1159/000333822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ketorolac Add-On Treatment on Intra-Ocular Pressure in Glaucoma Patients Receiving Prostaglandin Analogues

Abstract: Background/Aims: While topical ocular hypotensive agents cause secretion of endogenous prostaglandin (PG), systemic and topical non-steroidal anti-inflammatory agents inhibit its production; thus, they may interfere with therapeutic efficacy. This study aimed to investigate the effect of add-on treatment with ketorolac on intra-ocular pressure (IOP)-lowering effects of three different PG analogues. Methods: This study included 30 adult bilateral glaucoma patients who had been receiving PG analogues for primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
0
13
1
Order By: Relevance
“…Similarly, they reported that patients who were under latanoprost, travoprost, and bimatoprost treatment did not differ with regard the change in IOP. 22 Unlike this study, we have observed a significant IOP reduction within 1 hour, after the nepafenac was initiated. In addition, our study included only POAG patients, whereas the previous study included pseudoexfolation glaucoma patients.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Similarly, they reported that patients who were under latanoprost, travoprost, and bimatoprost treatment did not differ with regard the change in IOP. 22 Unlike this study, we have observed a significant IOP reduction within 1 hour, after the nepafenac was initiated. In addition, our study included only POAG patients, whereas the previous study included pseudoexfolation glaucoma patients.…”
Section: Discussioncontrasting
confidence: 77%
“…8,10,22 In contrast, Kashiwagi and colleagues 11,12 have reported that NSAID negatively interferes with latanoprost-induced IOP reduction. However, only healthy volunteers were included in Kashiwagi and Tsukahara's study, and Chiba and colleagues analyzed 9 POAG and 4 ocular hypertension patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of endogenous PG on IOP changes has been investigated, [10][11][12][13][14][15] no association of such activity with conjunctival hyperemia has been described. In this study, the inhibitive effect of topical ophthalmic NSAID on PG analog-related conjunctival hyperemia over the first 6 hours after TRZ instillation was seen on days 1 and 2, but this did not last the next 6 hours (ie, 20:00 of peak time).…”
Section: Discussionmentioning
confidence: 99%
“…9 Suppression of endogenous PG expression by oral medicines or ophthalmic solutions containing nonsteroidal anti-inflammatory drugs (NSAIDs) affects the change of IOP. [10][11][12][13][14][15] Besides, NSAIDs have found many useful applications, especially in inhibiting inflammation caused by synthesis of endogenous PG analog after intraocular operations. [16][17][18] Meanwhile the extent to which endogenous PG synthesized is associated with PG analog-related conjunctival hyperemia has not been reported currently.…”
mentioning
confidence: 99%
“…On the other hand, long-term macular edema would result in visual decline in patients. It is important to clarify whether IOP control is affected by concomitant treatment with topical NSAIDs and PG analogues in glaucoma patients or not [ 12 17 ]. Therefore, the aim of this study was to review previous articles and evaluate the influence of topical NSAIDs on IOP in glaucoma patients being treated with PG analogues via a literature review and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%